PENGARUH KEPEMIMPINAN KHARISMATIK DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD PROVINSI KALIMANTAN BARAT - Aprilia, Anggie B1021141116 (Jurnal Manajemen Update, 2020)
ABSTRAK The smooth implementation of government tasks and national development is highly dependent on the perfection of the state apparatus, especially Civil Servants (PNS). Therefore, in order to achieve the goals of national development that is to realize civil society and obey the law, modern civilization, democratic, prosperous, just, and highly moral, required Civil Servants who are elements of the state apparatus serving as state servants and public servants.In improving the way of working throughout the West Kalimantan Province SPKD, it requires firm leadership with a charismatic spirit that can be a role model for all subordinates in order to improve and create a good work culture so that all officials in the government of West Kalimantan Province can be disciplined in providing good services and high work performance. This study aims to examine the effect of charismatic leadership and organizational culture on employee performance. This type of research used in this study is causality research with multiple regression analysis analysis techniques. Data were obtained from 74 civil servants in the West Kalimantan Provincial Parliament Secretariat by distributing closed questionnaires.The results of this study indicate that the charismatic leadership variable (X1) has a significant effect on employee performance (Y) and organizational culture has a significant effect on employee performance (Y). Keyword : Charismatic Leadership, Organizational Culture, Performance DAFTAR PUSTAKA  Bangun, W. (2012). Manajemen Sumber Daya Manusia. Jakarta: Erlangga. Bilgin, N., & Isleyen, A. (2016). A Research on the relationship of charismatic leadership behaviors of agricultural cooperative managers with cooperative shareholders? performance and satisfaction. Chinese Business Review, Vol. 05 (04), 186-197. Fithriana, N., & Adi, A. N. (2017, Desember). Dominant Effect Between Compensation, Leadership and Organization Culture On Employee Performance Improvement. Journal of Applied Management, 15 (04), 670-676.Graha, A. M., & Rahardjo, E. (2016, December). Analisis Pengaruh Budaya Organisasi dan Kompensasi Terhadap Kinerja Dengan Motivasi Sebagai Variabel Intervening (Studi Kasus pada PT LG Bagian Penjualan Indonesia Semarang). Jurnal Studi Manajemen & Organisasi, 13, 98-109.Ivancevich, J. M, et al. (2007). Perilaku & Manajemen Organisasi. Jakarta: Erlangga.Nizamuddin., Sagal, S., & Napitupulu, E. (2018, January). Effect of Leadership, Organizational Structure, Compensation, and Motivation Toward Performance of Aggregat Data Control on The Statistics Center North Sumatera Province. International Journal of Education and Research, 06 (01), 167-180.Rantesalu, A., Mus, A. R., Mapparenta., & Arifin, Z. (2016). The Effect of Competence, Motivation and Organizational Culture On Employee Performance: the Mediating Role of Organizational Commitment. Journal of Research in Business and Management, 04 (09) 08-14.Rivai, V., Ramly, M., Mutis, T., & Arafah, W. (2014). Manajemen Sumber Daya Untuk Perusahaan: Dari Teori ke Praktik. Jakarta: Raja Grafindo Persada. Robbins, S. P. (2003). Prinsip-Prinsip Perilaku Organisasi, Edisi Kelima. Jakarta: Erlangga.